MULTIPLE INTERPRETATIONS OF IMAGES OF SPAIN IN THE VOCAL WORKS OF COMPOSERS: A COMPARATIVE ANALYSIS OF ROMANCES BASED ON THE PUSHKIN’S POEMS - Valentina L. Boiko (Russian Studies in Culture and Society)
Chamber vocal lyrics of Russian composers have been the subject of study for many researchers more than once. In this sense, the diversity of approaches and methods of study becomes interesting. One of them is the method of comparative analysis, which examines vocal works of different composers written to the same poem.